Epidemiology of hospital-acquired pneumonia: Results of a Central European multicenter, prospective, observational study compared with data from the European region - Herkel, Tomas; Uvizl, Radovan; Doubravska, Lenka; Adamus, Milan; Gabrhelik, Tomas; Htoutou Sedlakova, Miroslava; Kolar, Milan; Hanulik, Vojtech; Pudova, Vendula; Langova, Katerina; Zazula, Roman; Rezac, Tomas; et al. (Biomedical papers, 2016)
Background: Hospital-acquired pneumonia (HAP) is associated with high mortality. In Central Europe, there is a dearth of information on the prevalence and treatment of HAP. This project was aimed at collecting multicenter epidemiological data on patients with HAP in the Czech Republic and comparing them with supraregional data.Methods: This prospective, multicenter, observational study processed data from a database supported by a Czech Ministry of Health grant project. Included were all consecutive patients aged 18 and over who were admitted to participating intensive care units (ICUs) between 1 May 2013 and 31 December 2014 and met the inclusion criterion of having HAP. The primary endpoint was to analyze the relationships between 30-day mortality (during the stay in or after discharge from ICUs) and the microbiological etiological agent and adequacy of initial empirical antibiotic therapy in HAP patients.Results: The group dataset contained data on 330 enrolled patients. The final validated dataset involved 214 patients, 168 males (78.5%) and 46 females (21.5%), from whom 278 valid lower airway samples were obtained. The mean patient age was 59.9 years. The mean APACHE II score at admission was 21. Community-acquired pneumonia was identified in 13 patients and HAP in 201 patients, of whom 26 (12.1%) had early-onset and 175 (81.8%) had late-onset HAP. Twenty-two bacterial species were identified as etiologic agents but only six of them exceeded a frequency of detection of 5% (Klebsiella pneumoniae 20.4%, Pseudomonas aeruginosa 20.0%, Escherichia coli 10.8%, Enterobacter spp. 8.1%, Staphylococcus aureus 6.2% and Burkholderia cepacia complex 5.8%). Patients infected with Staphylococcus aureus had significantly higher rates of early-onset HAP than those with other etiologic agents. The overall 30-day mortality rate for HAP was 29.9%, with 19.2% mortality for early-onset HAP and 31.4% mortality for late-onset HAP. Patients with late-onset HAP receiving adequate initial empirical antibiotic therapy had statistically significantly lower 30-day mortality than those receiving inadequate initial antibiotic therapy (23.8% vs 42.9%). Patients with ventilator-associated pneumonia (VAP) had significantly higher mortality than those who developed HAP with no association with mechanical ventilation (34.6% vs 12.7%). Patients having VAP treated with adequate initial antibiotic therapy had lower 30-day mortality than those receiving inadequate therapy (27.2% vs 44.8%).Conclusions: The present study was the first to collect multicenter data on the epidemiology of HAP in the Central European Region, with respect to the incidence of etiologic agents causing HAP. It was concerned with relationships between 30-day patient mortality and the type of HAP, etiologic agent and adequacy of initial empirical antibiotic therapy.
Keywords: hospital-acquired pneumonia; mortality; HAP; VAP; antibiotic therapy